MEDIA PEMBELAJARAN TEKNOLOGI INFORMASI YANG MENUMBUHKAN MINAT BELAJAR AQIDAH AKHLAK DI SD UMP PURWOKERTO - Nugroho, Tato; Fauzi, Fauzi (Jurnal Ilmiah Mandala Education (JIME), 2022)
This study aims to explain the use of learning media to foster interest in learning from Aqidah Akhlak among students of SD UMP Purwokerto. This type of survey is a qualitative descriptive survey. Data obtained through observation, interviews and documentation. The results showed that the use of audiovisual learning media was very useful for learning activities, especially when learning Aqidah Akhlak. Learning with Google Meet Media, educational videos (YouTube), and Google Forms can really motivate your students. In addition, the use of learning media in SD UMP Purwokerto plays an important role in students' interest in learning. This includes a sense of pleasure and increased interest in teaching materials. The conclusion of this study is that teachers must be good at choosing the right media when providing learning materials in class, and creative and innovative teachers to make their students' learning environment more enthusiastic and motivated.